Application of the Bayesian Approach to Incorporate Helium Isotope Ratios in Long-Term Probabilistic Volcanic Hazard Assessments in Tohoku, Japan - Martin, Andrew James; Umeda, Koji; Ishimaru, Tsuneari (IntechOpen, 2012)
None